Tera Gymnastic to Decrease Anxiety of Elderly - M Nancye, Pandeirot; Darmawan, Taufan Citra; Husni, Amin; Ratna Sawitri, Dian (Universitas Airlangga, 2022)
Introduction: The most common mental problem in the elderly is anxiety. The elderly is anxious due to lack of activity and rest. Elderly need activities that diverse, interesting, and easy to practice. Tera gymnastics therapy is type of exercise, easy to apply and does not require a lot of time. Tera gymnastics can be applied to the elderly as an interesting and easy alternative to exercise. The purpose of this study was to explain the effect of tera exercise on reducing anxiety in the elderly. Method: This study uses pre-experimental design with one group pre-post-test model. The study population was 43 elderly people who were in